Supercompensation in elite water polo: Heart rate variability and perceived recovery - Botonis, P. G.; Smilios, I.; Toubekis, A. G. (Sports Medicine International Open, 2021)
We examined the association of heart rate variability assessed with the logarithm of the root mean square of successive differences (LnRMSSD) and perceived recovery status of nine elite water polo players with the fluctuations of the internal training load (ITL). ITL, post-wakening LnRMSSD, and measures of perceived recovery were obtained across one regeneration week, during two mesocycles of intensified preseason training (PR1, PR2) and during two mesocycles of in-season training (IN1, IN2). ITL at PR1 and PR2 was increased by 60-70% compared to regeneration week (p<0.01) and was reduced by 30% at IN1 and IN2 compared to PR1 and PR2 (p<0.01). Weekly averaged LnRMSSD (LnRMSSDmean) was higher in IN2 compared to regeneration week and PR2 (p<0.01 and p<0.05, respectively). Perceived recovery was higher at IN1 and IN2 compared to PR2 (p=0.01 and p<0.001, respectively). ITL correlated with LnRMSSD in the preseason (r=-0.26, p=0.03). Nonetheless, similar association was not apparent during the in-season period (r=0.02, p=0.88). Cardiac autonomic perturbations may not occur when an increment of internal training load is less than 60-70%. However, the reduction of training load in season by 30% improves both LnRMSSDmean and perceived recovery status, implying that training periodization may lead players in supercompensation.